2022
DOI: 10.1111/ddg.14666
|View full text |Cite
|
Sign up to set email alerts
|

Oral vitamin D versus acitretin in congenital non‐syndromic ichthyosis: double blinded, randomized controlled trial

Abstract: Background: Vitamin D has emerged as a promising treatment for congenital ichthyosis for which no comparative studies exist. Methodology:In this randomized, double-blinded study, patients with congenital ichthyosis received either Vitamin D 2000 IU/day (group A) or acitretin 0.5 mg/kg/day (group B) for 24 weeks. The primary outcome was improvement in the Visual Index for Ichthyosis Severity (VIIS) and Ichthyosis Area Severity Index (IASI). Secondary outcomes included Ichthyosis Quality of Life Index-32 (IQoL-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Therefore, despite the possibilities of retinoids’ protective effects on ischemic injury, there are studies that do not suggest retinoid therapy in infants and recommend not to preclude them to a surgical intervention [ 38 ]. A recent novel randomized controlled trial study proposed vitamin D intake as a promising alternative for managing congenital ichthyosis in comparison to acitretin [ 46 ]. In 2021, the scientific community published a consensus of recommendations regarding the safety of the topical and systemic administration of retinoids [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, despite the possibilities of retinoids’ protective effects on ischemic injury, there are studies that do not suggest retinoid therapy in infants and recommend not to preclude them to a surgical intervention [ 38 ]. A recent novel randomized controlled trial study proposed vitamin D intake as a promising alternative for managing congenital ichthyosis in comparison to acitretin [ 46 ]. In 2021, the scientific community published a consensus of recommendations regarding the safety of the topical and systemic administration of retinoids [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…36 Highdose vitamin D treatment has been therapeutic in ichthyosis, 37 with improvement in quality of life comparable to treatment with acitretin. 38 In inflammatory skin conditions such as atopic dermatitis and psoriasis, vitamin D is suggested to attenuate acute inflammation through modulation or inhibition of inflammatory cytokines, facilitating skin recovery. 39 Given Vitamin D's additional roles of keratinocyte differentiation and skin barrier formation, along with its impact on other skin conditions, further studies of the role of vitamin D in EB skin are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…4 In a novel randomized controlled trial study, vitamin D intake was proposed as a promising alternative for managing congenital ichthyosis compared to acitretin. 43 However, despite the protective effects of retinoids on ischemic injury, some studies do not suggest retinoid therapy in infants (and recommend not to preclude them to a surgical intervention). 44 Tsivilika et al suggested that, although applying topical retinoids have been suggested as an alternative to surgery, no satisfactory results have been seen in most cases.…”
Section: Discussionmentioning
confidence: 99%